The seven habits of highly effective people : restoring the character ethic - Covey, Stephen R (New York : Simon and Schuster, 1989)
This book "is a holistic, integrated approach to solving personal and professional problems by becoming 'principle-centered.' It is a revolutionalry guidebook to achieving peace of mind within and building trust without by seeking the roots of human behavior in character and by learning principles rather than merely practices. With pointed anecdotes and penetrating insights, Stephen R. Covey -- leading management consultant and author of best-selling spiritual books -- reveals how our actions follow from who we are. He shows how we can end self-defeating behavior at home and at work by adopting the Seven Habits of Higly Effective People. Covey shows how the Seven Habits are not a 'quick fix' but rather a step-bystep pathway to the principles of fairness, integrity, honesty, and human dignity that give us the security to adapt to change in our family and business lives -- as well as the wisdom and power to take advantage of the opportunities such change creates."
part 1. Paradigms and principles -- part 2. Private victory -- Habit 1: be proactice -- Habit 2: begin with the end in mind -- Habit 3: put first things first -- part 3. Public victory -- Habit 4: think win/win -- Habit 5: seek first to understand, then to be understood -- Habit 6: synergize -- part 4. Renewal -- Habit 7: Sharpen the saw
Includes indexes
Keywords: Success -- Psychological aspects; Character